Democracia, expertise e burocracia: relações entre política, técnica e participação - Frank de Paula Ribeiro (Ciências Sociais Unisinos, 2013)
This article provides a theoretical discussion concerning new models of democratic governance, focusing on the relationship between democracy, expertise and bureaucracy, especially with respect to connections between public administration, technical knowledge and participation. The concepts of expertise and expert, originating in Social Studies of Science and Technology (SSST), are applied to the analysis of the political control of bureaucracy in public administration, using as a reference model the public communication of science. Subsequently, a critique is made of the “public knowledge deficit” approach, a model that considers the public as composed of uninformed laypeople and whose fundamental task is to improve communication of knowledge from experts to the public in general. The article also considers the problematic model of “public participation” in the communication of science and technology, which recommends an equal relationship between experts and public participants and is adapted to interpret interactions of Deliberative Public Administration. Finally, it presents as an alternative the perspective of the “third wave” of SSST, proposing a compromise between the world of technical and scientific experts and the world of experience of the representatives of civil society in democratic decision-making arenas. This perspective is associated with participatory democracy, since it aims to recognize contributive expertise and expertise through interaction of both experts and representatives of society in interactions between public bureaucracy and civil society.